Denture adhesive
By developing a denture adhesive composition containing carboxymethylcellulose, crosslinked polyacrylic homopolymer and alkylvinyl ether-maleic acid copolymer, the problem of existing denture adhesives taking time to form retention after initial application, and by increasing the oil component and the petroleum component, the risk of leakage is reduced and better wear comfort and retention is achieved.
Patent Information
- Application Number
- CN202380050070.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-06-28
- Publication Date
- 2025-03-28
AI Technical Summary
Existing denture adhesives may take time to form good retention after initial application, and traditional denture adhesives are prone to leakage problems during use, affecting the usage experience.
A denture adhesive composition is developed, including carboxymethylcellulose, crosslinked polyacrylic acid homopolymer and alkylvinyl ether-maleic acid copolymer or salts thereof, to improve viscosity and retain properties by adjusting the proportion of the composition and adding oil and lipomate components.
The composition provides immediate, strong and long-lasting retention, reducing the risk of adhesive leakage and improving wear comfort and retention of dentures.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention relates to a denture adhesive composition. The composition comprises (a) carboxymethylcellulose, (b) a cross-linked polyacrylic acid homopolymer and (c) an alkyl vinyl ether maleic acid copolymer or a salt thereof. Advantageously, the composition provides immediate, strong and long-lasting retention. Background Art
[0002] A full or partial denture is a form of dental appliance intended to be worn in the oral cavity as a replacement that serves as a replacement for some or all teeth common to the oral cavity. When using a denture, an adhesive is typically used to help adhere the dental appliance to a surface of the oral cavity, such as the palate or gum ridge. This denture adhesive fixes or temporarily fixes the denture in the oral cavity, improving the retention of the denture, while also being releasable so that the denture wearer can remove the denture for cleaning and maintenance. It is also recommended to remove the denture at the end of the day. Denture adhesives can provide an improvement in the denture wearing experience, even if the denture fits well. Denture adhesives are also beneficial in situations where the denture may not fit perfectly, for example due to natural shrinkage and changes in the gums or oral mucosa over time.
[0003] Denture adhesive compositions (also called fixative compositions) fill the gap between the denture and the gums or tissues. Before the denture is placed in the mouth, the denture adhesive is applied to the surface of the denture plate (denture plate) to provide uniform contact with the gums and oral tissues.
[0004] Denture adhesive compositions need to meet many (sometimes competing) criteria in order to work effectively: they should produce a high degree of viscosity when in contact with saliva so that the denture can be held (fixed) in place once it is in the mouth, have sufficient cohesive strength to withstand the chewing stress that displaces the denture, and provide a seal to prevent food debris from entering under the denture. In addition, the sensory properties of the denture adhesive composition, such as mouthfeel and smoothness (consistency) should be acceptable to the user, and the composition should not be too messy or too sticky to apply. Denture adhesives are typically sold as creams (pastes), pads or strips, liquids, gels or powders, and examples are known in the art, including commercially available denture adhesives, such as POLIGRIP Flavour Free denture adhesive cream (GlaxoSmithKline), POLIGRIP Cushion and Comfort denture adhesive cream (GlaxoSmithKline) and Fixodent PLUS Best Hold Premium denture adhesive paste (P&G).
[0005] WO / 1992 / 22280 (Richardson Vicks, Inc.) discloses denture stabilizing compositions comprising mixed partial salts of lower alkyl vinyl ether-maleic acid copolymers.
[0006] WO / 2013 / 054236 (Procter and Gamble) discloses a denture adhesive comprising a mixture of partial salts of a copolymer of methyl vinyl ether-maleic acid, sodium carboxymethylcellulose and a cohesion builder component in an amount of about 0.001 wt % to about 10 wt % of the denture adhesive composition.
[0007] WO / 2016 / 091738 (Glaxo Group Ltd) discloses a denture adhesive composition comprising a lower alkyl vinyl ether-maleic acid copolymer, sodium carboxymethyl cellulose and a mixed partial salt of a bioactive glass.
[0008] WO / 2018 / 175826 (Lubrizol) discloses a composition comprising: (a) a cross-linked poly(acrylic acid) polymer in combination with (b) a carboxymethyl cellulose (CMC) component and / or (c) an adhesion promoting component. The cross-linked poly(acrylic acid) polymer may be a carbomer homopolymer, a carbomer copolymer, a carbomer interpolymer, a polycarbophil, or a mixture thereof.
[0009] Despite considerable effort over the years to develop denture adhesive compositions, there remains a need for further denture adhesives that provide an improved user experience. Summary of the invention
[0010] The present inventors have developed compositions having desirable adhesive properties, particularly for use in dental appliances such as dentures.
[0011] In a first aspect, a denture adhesive composition is provided, comprising: (a) carboxymethyl cellulose, (b) a cross-linked polyacrylic acid homopolymer, and (c) an alkyl vinyl ether maleic acid copolymer or a salt thereof. In particular, the denture adhesive composition comprises: (a) about 15 to about 30 wt % (wt % / wt (%W / wt)) of carboxymethyl cellulose, (b) about 6 to about 15 wt % (% wt / wt) of a cross-linked polyacrylic acid homopolymer, and (c) about 15 to about 34 wt % (% wt / wt) of an alkyl vinyl ether-maleic acid copolymer or a salt thereof.
[0012] The denture adhesive composition of the present invention may further include (d) an oil component and / or (e) a petrolatum (wax paste, vaseline, petrolatum) component. In particular, the denture adhesive composition of the present invention may include about 17 to about 56% by weight (% weight / weight) of an oil component, a petrolatum component, or a combination thereof.
[0013] In some embodiments, the denture adhesive composition of the present invention may include about 17 to about 56 wt % (% wt / wt) of an oil component. In some embodiments, the denture adhesive composition of the present invention may include about 17 to about 56 wt % (% wt / wt) of a petrolatum component. In particular, the denture adhesive composition of the present invention may include about 17 to about 26 wt % (% wt / wt) of an oil component and about 20 to about 30 wt % (% wt / wt) of a petrolatum component.
[0014] In particular, after preparation, the denture adhesive composition of the present invention has a viscosity of at least 500,000 centipoise (cP). In particular, after preparation, the viscosity of the denture adhesive composition of the present invention does not exceed 2,500,000 cP, more particularly does not exceed 2,000,000 cP. In particular, after preparation, the viscosity of the denture adhesive composition of the present invention is 500,000 to 2,500,000 centipoise (cP), more particularly 500,000-2,000,000 cP. In particular, the composition has a pH of 4.0 to 10, more particularly a pH of 5.0 to 8.0. More particularly, the denture adhesive composition of the present invention has (i) a viscosity of 500,000 to 2,000,000 centipoise (cP) and / or (ii) a pH of 4.0 to 10, more particularly a pH of 5.0 to 8.0. In particular, the viscosity is at 25°C. More specifically, viscosity is measured using a Brookfield RVT viscometer, TE spindle, 2.5 rpm at 25°C. Measured at 1°C.
[0015] In particular, the carboxymethylcellulose has a viscosity of about 1000 to about 2800 centipoise (cP) (measured in a 1% solution at 25°C). More particularly, the carboxymethylcellulose consists of fine particles, at least 80% of which pass through a 200 US mesh screen. In equivalent SI units, the carboxymethylcellulose consists of fine particles, at least 80% of which pass through a 74 μm mesh screen. Preferably, the carboxymethylcellulose is sodium carboxymethylcellulose. In particular, the denture adhesive composition of the present invention includes about 5 to about 10% by weight (% weight / weight) of a cross-linked polyacrylic acid homopolymer, particularly about 6 to about 9% by weight (% weight / weight) of a cross-linked polyacrylic acid homopolymer.
[0016] In particular, the crosslinked polyacrylic acid homopolymer is an allyl pentaerythritol crosslinked homopolymer. More particularly, the crosslinked polyacrylic acid homopolymer is a carbomer homopolymer of type A or type B. Still more particularly, the crosslinked polyacrylic acid homopolymer is selected from Carbomer 971P NF, Carbomer 974P NF and combinations thereof. Still more particularly, the crosslinked polyacrylic acid homopolymer is selected from Carbopol 971P NF, Carbopol 974P NF and combinations thereof. Preferably, the crosslinked polyacrylic acid homopolymer is Carbomer 971PNF, in particular Carbopol 971P NF.
[0017] Particularly, the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) salt. More particularly, the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt.
[0018] In certain embodiments, the denture adhesive composition comprises or consists essentially of:
[0019] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0020] (b) 6-10% w / w of a cross-linked polyacrylic acid homopolymer;
[0021] (c) 16-26% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0022] (d) 17-22% w / w of an oil component;
[0023] (e) 23% to 29% petrolatum; and optionally
[0024] (f) at least one fragrance (fragrance), colorant, preservative, surfactant or mixtures thereof; wherein the composition has a viscosity of 1,000,000 to 2,000,000 centipoise (cP) and a pH of 5.0 to 7.5.
[0025] In particular, the denture adhesive composition is free of polyethylene glycol, sodium alginate (sodium alginate) and / or zinc.Preferably, the denture adhesive composition of the present invention is free of polyethylene glycol, sodium alginate and zinc.
[0026] In a second aspect, there is provided a use of a denture adhesive composition according to the first aspect in a method of adhering a dental appliance to a surface, in particular a surface in the oral cavity. Also provided is a method of adhering a dental appliance to a surface, in particular a surface in the oral cavity, using a denture adhesive composition according to the first aspect. In particular, the method may comprise applying the composition of the first aspect to the dental appliance, the oral cavity, or both, and applying the dental appliance to a surface of the oral cavity, such as the palate or the gingival ridge. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 : Shown are the adhesion curves (adhesion characteristics) of Formulations 1-6 compared to a control formulation (POLIGRIP unflavored denture adhesive paste).
[0028] Figure 2 : Shown are the adhesion curves of Formulations 7 to 14 compared to a control formulation (POLIGRIP unflavored denture adhesive paste).
[0029] Figure 3 : Shown are the adhesion curves of Formulations 16, 17 and 20 compared to a control formulation (POLIGRIP unflavored denture adhesive paste).
[0030] Figure 4 : The effect of varying the ratio of mineral oil and petrolatum on the adhesion curves of formulations 22, 23 and 24 is shown.
[0031] Figure 5 : shows the adhesive layer thickness of formulations 22, 23 and 24 before and during compression. The formulations each maintained a higher layer thickness than the control ( Figure 5 (a)).
[0032] Figure 6 : Formulation 25 (measured at baseline and 0.5, 1, 3, 6, 9, and 12 hours after denture insertion ) and denture-free adhesives ( ) until the maxillary denture is displaced. Note that the error bars have been slightly offset to The left side of the symbol and symbols to help visualize and distinguish them more clearly. DETAILED DESCRIPTION
[0033] The present inventors have discovered improved denture adhesive compositions that solve many of the problems of currently available denture adhesives. The compositions provide immediate retention, helping to make the denture feel natural and comfortable in the mouth, avoiding concerns about traditional denture adhesives that may take time to develop good retention after initial application. In addition, the denture adhesive formulations provide strong and lasting retention. The material adheres to the gum ridge, in addition to providing adhesion properties, it also creates a buffering effect between the gums and the denture, thereby improving overall comfort. The denture adhesive formulations can also reduce the problem of seepage that may occur when the adhesive leaks from between the gum line and the denture into the mouth. The denture adhesive composition of the present invention comprises: (a) carboxymethyl cellulose, (b) a cross-linked polyacrylic acid homopolymer and (c) an alkyl vinyl ether-maleic acid copolymer or a salt thereof, wherein the pH of the composition is 5.0-8.0, particularly 5.0-7.5.
[0034] As used herein, the term "dental appliance" refers to dentures or partial dentures, artificial teeth, removable (detachable) orthodontic bridges and denture plates (upper and lower), orthodontic retainers and appliances, protective mouth guards, night guards (bite plates, bite pads) for preventing bruxism and / or temporomandibular joint (TMJ) disorders, etc. The term "denture" is used to refer to a subset of dental appliances, which includes dentures or partial dentures, such as upper and lower dentures and combinations thereof, including orthodontic bridges, artificial teeth, denture plates, etc.
[0035] The terms "denture adhesive composition" and "denture adhesive" are terms used in the art and relate to compositions used with dentures to enhance retention (retention), stability, and function.
[0036] For the avoidance of doubt, reference to "wt %" (% wt / wt) means that the amount of each ingredient is selected so that the total ingredients in the composition total 100 wt %, based on the weight of the total composition.
[0037] Carboxymethyl cellulose
[0038] The denture adhesive composition of the present invention includes carboxymethyl cellulose (CMC), a cellulose derivative. In particular, the composition includes about 15% to about 30% by weight of CMC, particularly about 20% to about 30% by weight, or more particularly about 26% to about 30% by weight of CMC. For example, 25%, 26%, 27%, 28%, 29% or 30% by weight of CMC. Preferably, the CMC is food grade or pharmaceutical grade CMC.
[0039] In particular, the CMC is provided in the form of a powder before being used in the composition of the present invention, more particularly in the form of a fine powder, more particularly in the form of a fine powder such that at least 99.9% of the particles of the fine powder pass through a 60 US mesh sieve, more particularly at least 90% of the particles pass through an 80 US mesh sieve, still more particularly at least 80% of the particles pass through a 100 US mesh sieve and still more particularly at least 80% of the particles pass through a 200 US mesh sieve. A 60 US mesh sieve is equivalent to a sieve with 250 micron openings. An 80 US mesh sieve is equivalent to a sieve with 177 micron openings. A 100 US mesh sieve is equivalent to a sieve with 149 micron openings. A 200 US mesh sieve is equivalent to a sieve with 74 micron openings. The term micron can be used interchangeably with the International System of Units (SI) term micrometer (μm). Thus, CMC is provided in the form of a fine powder of which at least 99.9% of the particles pass through a 250 μm mesh, more particularly at least 90% of the particles pass through a 177 μm mesh, still more particularly at least 80% of the particles pass through a 149 μm mesh and still more particularly at least 80% of the particles pass through a 74 μm mesh.
[0040] In particular, the CMC has a viscosity of about 800 to about 3000 centipoise (cP), preferably about 1000 to about 2800 cP (measured in a 1% solution at 25°C).
[0041] In particular, the CMC has a degree of substitution (DS) of about 0.65 to about 0.95, such as about 0.65 to about 0.85, preferably about 0.7.
[0042] Preferably, CMC is sodium carboxymethylcellulose. In particular, sodium carboxymethylcellulose has a sodium content of 6.5% to 9.5%, such as 7.0% to about 9.2%, more particularly about 7.0% to about 8.9%.
[0043] Preferably, the CMC is sodium carboxymethylcellulose having an average molecular weight of about 725,000.
[0044] Examples of commercially available CMCs that can be used in the compositions of the present invention include 7H products available from Aquaion, such as 7H3SXF or 7H3SF, and products available from Dupont, such as WALOCEL CRT 2000, WALOCEL CRT 10000, or WALOCEL CRT 15000, such as WALOCEL CRT 15000 PPA (S) Sodium. In certain embodiments, the sodium CMC is sodium CMC 7H3SXF, 7H3SF, 7H3SXF PH, 7H3SF PH, WALOCEL CRT 15000, WALOCEL CRT 15000 PPA (S) Sodium, or an equivalent.
[0045] In certain embodiments, the sodium carboxymethylcellulose is food grade or pharmaceutical grade CMC having a viscosity of about 1000 to about 2800 cP (measured in a 1% solution at 25° C.), a degree of substitution of about 0.65 to about 0.95, a sodium content of 6.5% to 9.5%, and an average molecular weight of about 725,000.
[0046] Cross-linked polyacrylic acid homopolymer
[0047] The denture adhesive composition of the present invention includes a cross-linked polyacrylic acid homopolymer, generally referred to by the generic term "carbomer". Carbomers are high weight polymers of acrylic acid cross-linked with allyl sucrose or allyl ethers of pentaerythritol, containing 56% to 68% carboxylic acid (-COOH) groups and 0.75% to 2% cross-linking agent. Upon contact with water, carbomers readily absorb water and swell as they become hydrated.
[0048] In particular, the composition comprises from about 4% to about 15% by weight of a crosslinked polyacrylic acid homopolymer, in particular from about 5% to about 10% by weight, or more particularly from about 6% to about 9% by weight of a crosslinked polyacrylic acid homopolymer, for example 4%, 5%, 6%, 7%, 8% or 9% by weight of a crosslinked polyacrylic acid homopolymer.
[0049] In particular, the cross-linked polyacrylic acid homopolymer is an allyl pentaerythritol cross-linked homopolymer. More particularly, the cross-linked polyacrylic acid homopolymer is an allyl pentaerythritol cross-linked homopolymer polymerized in ethyl acetate. The cross-linked polyacrylic acid homopolymer can be an A-type or B-type carbomer homopolymer. In some embodiments, the cross-linked polyacrylic acid homopolymer is an A-type carbomer homopolymer. In some embodiments, the cross-linked polyacrylic acid homopolymer is a B-type carbomer homopolymer.
[0050] In particular, the cross-linked polyacrylic acid homopolymer is of food grade and / or pharmaceutical grade and is provided in the form of a free-flowing powder, more particularly in the form of a fine free-flowing powder, prior to use in the composition of the invention.
[0051] In certain embodiments, the CAS number of the cross-linked polyacrylic acid homopolymer is 9003-01-4. In particular, the carbomer has the chemical formula: C3H4O2. Preferably, the cross-linked polyacrylic acid homopolymer is selected from carbomer 971, carbomer 974 and combinations thereof. More preferably, the cross-linked polyacrylic acid homopolymer is carbomer 971 or carbomer 974. In a preferred embodiment, the cross-linked polyacrylic acid homopolymer is carbomer 971. More particularly, the carbomer is a pharmaceutical grade form of carbomer 971 (referred to as carbomer 971P) for oral or mucosal contact. In particular, the carbomer is carbomer 971P NF, wherein "NF" indicates that the carbomer complies with the restrictions cited in the current edition of the USP / NF "Carbomer Homopolymer Type A" and the European Pharmacopoeia (Ph.Eur.) "Carbomers" monograph. In certain embodiments, Carbomer 971 has a viscosity of 4000 to 11,000 cP, particularly about 7200 cP (25°C Brookfield RVT, 20 rpm, neutralized to pH 7.3-7.8, 0.5 wt% mucus, spindle #5 (<10,000 cP) or spindle #6 ( 10,000 cP)); a carboxylic acid content of 56.0% to 68.0%, in particular about 59.6%; an acrylic acid content (in ppm) of <1000 ppm, in particular less than 100 ppm, for example about 80 ppm and an ethyl acetate content of <0.50%, for example about 0.41%.
[0052] Suitable commercially available forms of Carbomer 971 or Carbomer 974 are available from LUBRIZOL, such as CARBOPOL 971P NF and CARBOPOL 974P NF, or from COREL PHARMA, such as ACRYPOL 971 and ACRYPOL 974. In a particular embodiment, the cross-linked polyacrylic acid homopolymer is CARBOPOL 971P NF.
[0053] Alkyl vinyl ether-maleic acid copolymer
[0054] The denture adhesive composition of the present invention includes an alkyl vinyl ether-maleic acid (AVE / MA) copolymer or a salt thereof, such as a mixed salt, a partial salt, or a mixed partial salt. As used herein, the term "mixed salt" refers to a salt in which at least two different cations are mixed with each other or with other salts on the same polymer. The term "partial salt" refers to a salt of a polymer in which less than 100% of the acid groups are reacted.
[0055] In particular, the denture adhesive composition includes an alkyl vinyl ether-maleic acid copolymer partial salt. More particularly, the denture adhesive composition includes an alkyl vinyl ether maleic acid copolymer mixed partial salt.
[0056] The alkyl vinyl ether-maleic acid copolymer comprises at least one cationic salt selected from strontium, zinc, iron, magnesium, calcium and sodium. Preferably, the alkyl vinyl ether-maleic acid copolymer comprises at least one cationic salt selected from calcium and sodium. Therefore, in some embodiments, the AVE / MA copolymer comprises a cationic salt selected from calcium and sodium or a combination thereof. Preferably, at least one cationic salt is a combination of calcium and sodium cations.
[0057] The metal cation can provide an amount of about 10.0% to about 20.0% of the metal cation to be present on the alkyl vinyl ether-maleic acid copolymer, such as about 12.0% to about 16.0%, for example about 12.0%, about 12.5%, about 13.0%, about 13.5%, about 14.0%, about 14.5%, about 15.0% or about 15.5%. In particular, the alkyl vinyl ether-maleic acid copolymer includes or is composed of: about 1.0% to about 15.0% of calcium cations and about 0.5% to about 5.0% of sodium cations. More particularly, the alkyl vinyl ether-maleic acid copolymer includes or is substantially composed of: about 9.0% to about 15.0% of calcium cations and about 1.0% to about 3.0% of sodium cations. Preferably, the alkyl vinyl ether-maleic acid copolymer does not contain zinc cations.
[0058] Suitably, the alkyl vinyl ether-maleic acid copolymer will have a molecular weight of at least 900,000 Daltons. In certain embodiments, the molecular weight is from about 1,000,000 to about 3,000,000.
[0059] In particular, the denture adhesive composition includes about 15 to about 34% by weight of alkyl vinyl ether-maleic acid copolymer or its salt. More particularly, the denture adhesive composition includes about 15 to about 26% by weight of alkyl vinyl ether-maleic acid copolymer or its salt. Still more particularly, the denture adhesive composition includes about 15 to about 22% by weight of alkyl vinyl ether-maleic acid copolymer or its salt. Still more particularly, the denture adhesive composition includes about 16% by weight to about 20% by weight of alkyl vinyl ether-maleic acid copolymer or its salt, such as about 16% by weight, about 17% by weight, about 18% by weight, about 19% by weight or about 20% by weight.
[0060] Preferably, the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) salt. More preferably, the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt.
[0061] Examples of suitable commercially available alkyl vinyl ether-maleic acid copolymers are sold under the trade name GANTREZ (ISP Investments LLC) and are available from Thermo Fisher or Ashland. These include GANTREZ AN (anhydride) forms such as Gantrez AN 169 (copolymer of methyl vinyl ether / maleic anhydride) and GANTREZ MS forms such as Gantrez MS-955 (mixed sodium and calcium salts of a copolymer of methyl vinyl ether and maleic anhydride).
[0062] Other components
[0063] The denture adhesive composition of the present invention may further include (d) an oil component and / or (e) a petrolatum component. The oil that can be used in the composition of the present invention may have a viscosity of about 10 centistokes (cSt, mm2) at 40°C. 2 The kinematic viscosity of the present invention is preferably a kinematic viscosity of about 10 cSt to about 240 cSt at 40° C., more particularly about 10 cSt to about 100 cSt at 40° C., or still more particularly about 10 cSt to about 90 cSt at 40° C. The kinematic viscosity can be measured at 40° C. by a calibrated glass capillary viscometer as described in ASTM Standard Test Method for Kinematic Viscosity of Transparent and Opaque Liquids D445 (DOI: 10.1520 / D0445-21E01).
[0064] By way of non-limiting example, suitable oils for use in the compositions of the present invention include light mineral oil, medium mineral oil, vegetable oils such as olive oil, oleic acid, sesame oil, safflower oil, corn oil, soybean oil, cottonseed oil, castor oil, palm oil and coconut oil.
[0065] Preferably, the oil component is selected from light mineral oil, medium mineral oil and combinations thereof.
[0066] Mineral oils can be characterized according to their kinematic viscosity. Light mineral oils typically have a kinematic viscosity of about 34 cSt or less at 40°C. Medium and heavy mineral oils typically have a kinematic viscosity at 40°C ranging from about 35 cSt to about 240 cSt.
[0067] In certain embodiments, the oil component is a medium mineral oil. In certain embodiments, the oil is a medium mineral oil, more particularly a medium mineral oil having a motion rate of about 35 cSt to about 90 cSt at 40°C, and still more particularly a medium mineral oil having a motion rate of about 63 cSt to about 80 cSt at 40°C. Suitable medium mineral oils include PIONIER 2071P or equivalent.
[0068] In certain embodiments, the oil component is a light mineral oil. In certain embodiments, the oil is a light mineral oil, more particularly a light mineral oil having a mobility of about 10 cSt to about 34 cSt at 40°C, still more particularly a medium mineral oil having a mobility of about 10 cSt to about 20 cSt at 40°C, still more particularly a medium mineral oil having a mobility of about 14 cSt to about 17 cSt at 40°C. Suitable light mineral oils include BLANDOL white mineral oil or equivalent.
[0069] Medium mineral oil (as defined above) is preferably used in the present invention. The term "petrolatum" is a term used in the art to refer to a semi-solid mixture of hydrocarbons. The viscosity of petrolatum can be measured using the ASTM standard test method for petrolatum cone penetration (D937-07) to determine the permeability of petrolatum as an empirical measure of consistency. Petrolatum can have a cone penetration consistency value (mm / 10, at 25°C) of about 10 to about 500, particularly about 25 to about 300, and more particularly about 50 to about 250. Preferably, petrolatum has a cone penetration consistency value (mm / 10, at 25°C) of about 100 to about 200, more preferably about 130 to about 195.
[0070] In particular, the denture adhesive composition of the present invention may include from about 10 to about 56 wt % (% wt / wt) of an oil component and / or a petrolatum component, more particularly from about 17 to about 56 wt % (% wt / wt) of an oil component and / or a petrolatum component.
[0071] In some embodiments, the denture adhesive compositions of the present invention may include from about 17 to about 56 wt % (% wt / wt) of an oil component. In some embodiments, the denture adhesive compositions of the present invention may include from about 17 to about 56 wt % (% wt / wt) of a petrolatum component.
[0072] In particular, the denture adhesive composition of the present invention may include an oil component of about 17 to about 26% by weight (% weight / weight) and a petrolatum component of about 20 to about 30% by weight (% weight / weight). More particularly, the denture adhesive composition of the present invention may include an oil component of about 18 to about 22% by weight (% weight / weight) and a petrolatum component of about 20 to about 27% by weight (% weight / weight). Still more particularly, the denture adhesive composition of the present invention may include an oil component of about 18 to about 22% by weight (% weight / weight) and a petrolatum component of about 23 to about 27% by weight (% weight / weight). Still more particularly, the denture adhesive composition of the present invention may include an oil component of about 18 to about 22% by weight (% weight / weight), such as about 18%, about 19%, about 20%, about 21% or about 22% by weight of an oil component, and about 23 to about 27% by weight (% weight / weight), such as about 23%, about 24%, about 25%, about 26% or about 27% by weight of a petrolatum component. In a preferred embodiment, the denture adhesive composition of the present invention comprises about 18% by weight (% weight / weight) of the oil component and about 25% by weight (% weight / weight) of the petrolatum component. In a further preferred embodiment, the denture adhesive composition of the present invention comprises about 18% by weight (% weight / weight) of the medium mineral oil component and about 25% by weight (% weight / weight) of the petrolatum component.
[0073] Sensory components
[0074] Denture adhesive compositions may include at least one sensory component. "Sensory component" refers to a component that can be used to impart flavor, fragrance, color and / or sensation (e.g., cool, warm or tingling) to the composition. In addition to imparting the desired sensory properties to the composition consumer, sensory components are generally not active components, in other words, they do not play an active role in adhesion, retention time or buffering. In particular, the sensory component is at least one flavoring, fragrance and / or coloring agent. Sensory components are known in the art and can be natural or artificial (synthetic).
[0075] The compositions of the present invention may include from about 0.01% to about 5% by weight of sensory components, specifically from about 0.01% to about 2% by weight of sensory components.
[0076] Flavoring agents known in the field of denture adhesives can be added to the composition of the present invention. These flavoring agents include, but are not limited to, synthetic flavoring oils and / or oils derived from plants, leaves, flowers, fruits, etc., and combinations thereof. Representative flavoring oils include spearmint oil, cinnamon oil, wintergreen oil (methyl salicylate) and peppermint oil. Artificial, natural or synthetic fruit flavoring agents are also useful, such as citrus oils (including lemon, orange, grape, lime and grapefruit), and fruit flavors (including apple, strawberry, cherry, pineapple, etc.). Flavoring agents can be liquid, spray-dried, encapsulated or adsorbed on a carrier, and mixtures thereof. On the one hand, the flavoring agent is peppermint oil. The amount of the flavoring agent used varies according to factors such as flavoring agent type, adhesive composition and required strength. On the one hand, the denture adhesive composition includes about 0.01% by weight to about 3.0% by weight of flavoring agent. On the other hand, the denture adhesive composition includes about 0.01% by weight to about 2.0% by weight of flavoring agent. In another aspect, the denture adhesive composition includes from about 0.05% to 2.0% by weight of a flavoring agent.
[0077] Denture adhesive compositions may also include the use of sweeteners well known in the art. Sweeteners may be selected from a wide range of materials, including water-soluble agents, water-soluble artificial sweeteners, and dipeptide-based sweeteners, including mixtures thereof. Representative sweeteners include, but are not limited to (a) sugar alcohols, such as sorbitol, xylitol, mannitol, maltitol, hydrogenated starch hydrolysates, and mixtures thereof; (b) water-soluble artificial sweeteners, such as soluble saccharin salts, i.e., sodium or calcium saccharin salts, cyclamates (cyclamate), acesulfame-K, sucralose, etc., and saccharin in free acid form; (c) dipeptide-based sweeteners, such as L-aspartyl-L-phenylalanine methyl ester, etc.; and (d) natural sweeteners, such as stevioside (stevia). On the one hand, the denture adhesive composition includes about 0.001% by weight to about 5.0% by weight of sweetener.
[0078] Colorants that can be used in the present invention include pigments and dyes suitable for food, drug and cosmetic applications. These colorants are referred to as FD&C (food, drug and cosmetic) and D&C (drug and cosmetic) dyes and lakes. Illustrative examples include, but are not limited to, D&C Red #30 aluminum lake paste, D&C Red #7 calcium lake paste, erythrosine lake paste, indigo dye (referred to as FD&C Blue No. 2, which is the disodium salt of 5,5-indigo disulfonic acid); FD&C Green No.1, including triphenylmethylene dyes and being 4-[4-N-ethyl-p-sulfobenzylamino) diphenylmethylene]-[1-(N-ethyl-N-p-sulfobenzyl)-2,5-cyclohexadienimine] monosodium salt. In some embodiments, the colorant is FD&C Red No.3. In some embodiments, the denture adhesive composition includes about 0 wt % to about 0.2 wt % of the colorant.
[0079] In a preferred embodiment, the denture adhesive composition is free of flavoring, fragrance and / or coloring agents.
[0080] The denture adhesive composition of the present invention can be dispensed by the consumer from a multi-dose package, pump or tube. Alternatively, the denture adhesive composition of the present invention can be pre-dispensed in a single-dose package, for example on a non-adhesive self-supporting layer that can be peeled off to enable the adhesive to be applied.
[0081] For ease of dispensing, the denture adhesive composition of the present invention may have a viscosity of 500,000-2,500,000 centipoise (cP), more particularly 1,000,000 to 2,000,000 cP, when measured after preparation of the composition. For the avoidance of doubt, the viscosity may be measured within two months after preparation of the composition, more particularly within one month after preparation of the composition, for example, when measured within one month after preparation of the composition, the viscosity is 1,000,000 to 2,000,000 cP. In particular, the viscosity is 25°C. More specifically, the viscosity is measured using a Brookfield RVT viscometer, TE spindle, 2.5 rpm, at 25°C. Measured at 1° C. The composition of the invention preferably has a pH in the range of 4.0 to 10.0, such as a pH in the range of 5.0 to 8.0, preferably a pH of about 5.0 to about 7.5, such as a pH of about 5.2 to about 7.1.
[0082] Typically, the composition of the present invention is stable at a temperature of 25°C for at least 3 months, particularly at a temperature of 25°C for at least 6 months, more particularly at a temperature of 25°C for at least 12 months, still more particularly at a temperature of 25°C for at least 24 months, and still more particularly at a temperature of 25°C for 36 months. As used herein, the term "stable" refers to the ability of a composition to maintain certain physical or chemical properties, such as adhesion, for a period of time at a specific storage temperature after production. The stability of the composition of the present invention can be assessed using standard methods known in the art.
[0083] In particular, the ratio of (a) carboxymethyl cellulose, (b) cross-linked polyacrylic acid homopolymer and (c) alkyl vinyl ether-maleic acid copolymer or its salt in the denture adhesive composition is 54% w / w (i.e., (a) + (b) + (c) = 54% w / w).
[0084] In particular, the denture adhesive composition does not contain polyethylene glycol, sodium alginate and / or zinc. Preferably, the denture adhesive composition of the present invention does not contain polyethylene glycol, sodium alginate and zinc. In particular, the denture adhesive composition of the present invention does not include SiO2.
[0085] The present invention provides the use of the denture adhesive composition of the present invention in a method of adhering a dental appliance to a surface, particularly a surface in the oral cavity. Also provided is a method of adhering a dental appliance to a surface, particularly a surface in the oral cavity, using the denture adhesive composition of the present invention.
[0086] In particular, the method may comprise applying the composition of the first aspect to a dental appliance, the oral cavity, or both, and applying the dental appliance to a surface of the oral cavity, such as the palate or the gingival ridge.
[0087] General
[0088] The term "comprising" encompasses "including," e.g., a composition "comprising" X may include others, e.g., X+Y. In some embodiments, the term "comprising" refers to including the indicated active agent, e.g., the listed compound, as well as including other active agents and carriers, excipients, emollients, stabilizers, and the like that are known and generally recognized as safe (GRAS) in the consumer health industry. The use of the transitional phrase "consisting essentially of..." means that the scope of the claim should be interpreted to cover the specified materials or steps described in the claim, as well as those materials or steps that do not materially affect the basic and novel features of the claimed invention. See In re Herz, 537 F.2d 549, 551-52, 190 USPQ461, 463 (CCPA 1976) (emphasis in original); see also MPEP 2111.03. Therefore, when used in the claims of the present invention, the term "consisting essentially of" is not intended to be interpreted as equivalent to "comprising". The term "consisting of" and its variations mean including and limited to (e.g., the specifically recited ingredients or steps). In some areas, the term "comprising an active ingredient consisting of" may be used in place of "consisting essentially of". The term "about" in connection with a numerical value x is optional and means, for example, that the numerical value may include some variance around the stated number to allow for routine experimental fluctuations, measurement variance, or to cover minor deviations that may achieve substantially the same result as the stated number, e.g., x 10%, x 5%, x 4%, x 3%, x 2% or x 1%. The word "substantially" does not exclude "completely", for example, a composition "substantially free of" Y may be completely free of Y. If necessary, the word "substantially" may be omitted from the definition of the present invention. Unless otherwise indicated, all percentages and ratios used herein are by weight of the total composition.
[0089] All references or patent applications cited in this patent specification are incorporated herein by reference.
[0090] Embodiments of the present invention
[0091] The following clauses describe certain embodiments of the invention:
[0092] Embodiment 1: A denture adhesive composition comprising or consisting essentially of:
[0093] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0094] (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer;
[0095] (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0096] (d) 17-22% w / w of an oil component;
[0097] (e) 23%-29% petrolatum; and optionally
[0098] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0099] Embodiment 2: A denture adhesive composition comprising or consisting essentially of:
[0100] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0101] (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer;
[0102] (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0103] (d) 17-22% w / w of an oil component;
[0104] (e) 23%-29% petrolatum; and optionally
[0105] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof;
[0106] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (cP at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0107] Embodiment 3: A denture adhesive composition comprising or consisting essentially of:
[0108] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0109] (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer;
[0110] (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0111] (d) 18-22% w / w of an oil component; and
[0112] (e) 23% to 27% petrolatum.
[0113] Embodiment 4: A denture adhesive composition comprising or consisting essentially of:
[0114] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0115] (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer;
[0116] (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0117] (d) 18-22% w / w of an oil component;
[0118] (e) 23%-27% petrolatum;
[0119] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0120] Embodiment 5: A denture adhesive composition comprising or consisting essentially of:
[0121] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0122] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0123] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0124] (d) 17-22% w / w of an oil component;
[0125] (e) 23%-29% petrolatum;
[0126] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0127] Embodiment 6: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0128] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0129] (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer;
[0130] (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid);
[0131] (d) 17-22% w / w of an oil component;
[0132] (e) 23% to 29% petrolatum;
[0133] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0134] Embodiment 7: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0135] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0136] (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer;
[0137] (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid);
[0138] (d) about 17% w / w of an oil component;
[0139] (e) about 29% petrolatum;
[0140] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0141] Embodiment 8: A denture adhesive composition comprising or consisting essentially of:
[0142] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0143] (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer;
[0144] (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid);
[0145] (d) about 21% w / w of an oil component;
[0146] (e) about 25% petrolatum;
[0147] Embodiment 9: A denture adhesive composition comprising, consisting essentially of, or consisting of:
[0148] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0149] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0150] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0151] (d) 17-22% w / w of an oil component;
[0152] (e) 23%-29% petrolatum;
[0153] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0154] Embodiment 10: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0155] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0156] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0157] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0158] (d) about 17% w / w of an oil component;
[0159] (e) about 29% petrolatum;
[0160] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0161] Embodiment 11: A denture adhesive composition comprising or consisting essentially of:
[0162] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0163] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0164] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0165] (d) about 21% w / w of an oil component;
[0166] (e) about 25% petrolatum;
[0167] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0168] Embodiment 12: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0169] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0170] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0171] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0172] (d) about 17% w / w of an oil component;
[0173] (e) about 29% petrolatum; and optionally
[0174] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0175] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0176] Embodiment 13: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0177] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0178] (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer;
[0179] (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid);
[0180] (d) about 17% w / w of an oil component;
[0181] (e) about 29% petrolatum; and optionally
[0182] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0183] The composition has a viscosity of 1,000,000 to 2,000,000 centipoise (at 25°C). 1°C) and a pH of 5.0 to 7.5.
[0184] Embodiment 14: A denture adhesive composition comprising, consisting of, or consisting essentially of:
[0185] (a) 26-30% w / w sodium carboxymethyl cellulose;
[0186] (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer;
[0187] (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0188] (d) 17-23% w / w of an oil component;
[0189] (e) 23% to 29% petrolatum; and optionally
[0190] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0191] Embodiment 15: The denture adhesive composition of embodiment 14, wherein the composition has a pH of 4.0 to 10, specifically a pH of 5.0 to 8.0.
[0192] Embodiment 16: The denture adhesive composition of embodiment 14 or 15, wherein when measured within two months after preparation (at 25°C The composition has a viscosity of 500,000-2,500,000 centipoise (cP), specifically 500,000-2,000,000 centipoise (cP) when measured at 1°C.
[0193] Embodiment 17: The denture adhesive composition of Embodiments 14-16, wherein the carboxymethyl cellulose has a viscosity of about 1000 to about 2800 centipoise (cP) (measured in a 1% solution at 25°C).
[0194] Embodiment 18: The denture adhesive composition of Embodiment 17, wherein the carboxymethyl cellulose consists of fine particles, at least 80% of which pass through a 200 US mesh sieve (equivalent to a 74 μm mesh sieve).
[0195] Embodiment 19: The denture adhesive composition of Embodiment 17 or 18, wherein the cross-linked polyacrylic acid homopolymer is an allyl pentaerythritol cross-linked homopolymer.
[0196] Embodiment 20: The denture adhesive composition of embodiment 19, wherein the cross-linked polyacrylic acid homopolymer is a type A or type B carbomer homopolymer.
[0197] Embodiment 21: The denture adhesive composition according to embodiment 20, wherein the cross-linked polyacrylic acid homopolymer is Carbomer 971P NF and / or Carbomer 974P NF, in particular Carbomer 971P NF and / or Carbomer 974P NF.
[0198] Embodiment 22: The denture adhesive composition of any one of Embodiments 18-21, wherein the alkyl vinyl ether-maleic acid copolymer or its salt is a poly(methyl vinyl ether / maleic acid) salt.
[0199] Embodiment 23: The denture adhesive composition according to embodiment 22, wherein the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt.
[0200] Embodiment 24: The denture adhesive composition of embodiment 23, comprising, consisting of, or consisting essentially of:
[0201] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0202] (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer;
[0203] (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt;
[0204] (d) about 21% w / w of an oil component;
[0205] (e) about 25% petrolatum; and optionally
[0206] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0207] Embodiment 25: The denture adhesive composition of embodiment 23, comprising, consisting of, or consisting essentially of:
[0208] (a) about 28% weight / weight sodium carboxymethyl cellulose;
[0209] (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer;
[0210] (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid);
[0211] (d) about 21% w / w of an oil component;
[0212] (e) about 25% petrolatum; and optionally
[0213] (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
[0214] Embodiment 26: The denture adhesive composition of Embodiment 24 or 25, wherein the composition has a viscosity (at 25°C) of 1,000,000 to 2,000,000 centipoise. 1°C) and a pH of 5.0 to 7.5.
[0215] Embodiment 27: The denture adhesive composition of any one of Embodiments 1 to 26, wherein the composition is free of polyethylene glycol, sodium alginate, and zinc.
[0216] In order to better understand the present invention, the following examples are described. These examples are for illustrative purposes only and should not be construed as limiting the scope of the present invention in any way.
[0217] Example
[0218] Example 1: Denture Adhesive Composition I
[0219] Six formulations were prepared using commercially available ingredients. The formulations were based on the commercially available product POLIGRIP Buffered Comfort Denture Adhesive Paste (comprising: cellulose gum, paraffin liquid, petrolatum, carbomer, silica, white wax, fragrance and limonene), adapted to incorporate a poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt component to increase retention properties:
[0220]
[0221] *Poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt
[0222] Briefly, the petrolatum component was melted, the mineral oil component was added, and then the melted beeswax was added under stirring. Carbomer, sodium carboxymethylcellulose, sodium-calcium mixed part salt of poly(methyl vinyl ether / maleic acid), and Cab-o-sil M5 were then added in powder form under stirring. The composition was cooled and the flavoring components (Frescolat, spearmint oil, and peppermint oil) were added. After further mixing, the formulation was degassed.
[0223] To compare the adhesion curves (adhesion characteristics) of denture adhesives, an Instron texture analyzer (5943) (Instron, UK) equipped with a BioPuls bath and a 500N load cell was used. A certain amount of adhesive was placed on the test surface of the texture analyzer, compressed to a uniform thickness of 1 mm across the test surface, and then subjected to multiple compression / stretch cycles. After the compression / stretch cycle, the crosshead was quickly moved apart at a speed of 6 lbf / min, and the maximum tensile force was recorded. At least 20 times were repeated for each sample.
[0224] None of the formulation options improved retention properties sufficiently to match the control formulation (POLIGRIP unflavored denture adhesive paste, which contains a sodium-calcium mixed partial salt but no Carbopol) ( Figure 1 Adding 14% w / w or less of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt to the formulation was not sufficient to improve the adhesion properties.
[0225] Example 2: Effect of Carbomer on Viscosity
[0226] Eight additional formulations were prepared using commercially available ingredients. The formulations were based on the commercially available product POLIGRIP Unflavored Denture Adhesive Paste (comprising calcium / sodium PVM / MA copolymer, petrolatum, cellulose gum, and paraffin liquid), which was adapted to incorporate a carbomer component:
[0227]
[0228] *Poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt
[0229] The formulation was prepared in a similar manner as described in International Patent Application Publication No. WO16091738. Briefly, the petrolatum component was melted and the mineral oil component was added under stirring. Next, carbomer, sodium carboxymethylcellulose, and poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt were added in powder form under stirring. The composition was cooled and degassed.
[0230] The initial viscosity of the formulations was measured using a controlled stress rheometer (CarriMed CSL500) in dynamic mode with a cone-plate configuration in constant strain mode at 37° C. with an angular velocity of 10 rad / s. Five separate specimens were measured for each formulation.
[0231] The viscosity of formulations including at least 18% w / w carbomer component was very high (>4,000,000 cPs). Formulations 13 and 14, including 36% w / w and 54% w / w carbomer, respectively, were too thick to be properly formulated and tested.
[0232] Formulations including greater than 18% w / w of carbomer have viscosities that make them unsuitable for general use because they are difficult to formulate and / or difficult for the consumer to squeeze out of a dispenser (e.g., a tube). Therefore, it was determined that commercially desirable formulations should contain less than 18% w / w of carbomer.
[0233] Example 3: Denture Adhesive Composition II
[0234] Seven additional formulations were prepared using commercially available ingredients. The formulations were based on the commercially available product POLIGRIP Unflavored Denture Adhesive Paste (comprising calcium / sodium PVM / MA copolymer, petrolatum, cellulose gum, and liquid paraffin), which was adapted to incorporate carbomer, reduced AVE / MA levels, and varying amounts of CMC while maintaining acceptable viscosity properties:
[0235]
[0236] *Poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt
[0237] Formulations were prepared as described previously.
[0238] To compare the adhesion properties of denture adhesives, an Instron Texture Analyzer (5943) (Instron, UK) equipped with a BioPuls bath and a 500 N load cell was used. A certain amount of adhesive was placed on the test surface of the texture analyzer, compressed to a uniform thickness of 1 mm across the test surface, and then subjected to multiple compression / tension cycles.
[0239] After the compression / tension cycle, the crosshead was moved apart at a rate of 6 lbf / min and the maximum tensile force was recorded. This was repeated at least 20 times for each sample.
[0240] Results for formulations including 4% Carbopol showed suboptimal performance compared to the control. However, several formulations showed comparable or improved retention performance over existing commercial formulations ( Figure 2 ).
[0241] The formulation including 8% Carbopol and 18% poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt had the highest biopuls peak, while the formulation including 6% Carbopol and 20% poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt showed similar performance to the commercial formulation. Both formulations showed higher adhesion work scores ( Figure 3 ).
[0242] Example 4: Mineral Oil and Petrolatum
[0243] Based on the positive in vitro data on retention and viscosity, formulations 16 (6% Carbomer / 20% AVE / MA / 28% CMC) and 17 (8% Carbomer / 18% AVE / MA / 28% CMC) were selected for further work.
[0244] Petrolatum and mineral oil levels were varied to determine the effects on adhesion and viscosity.
[0245]
[0246] Increasing the proportion of mineral oil while decreasing the proportion of petrolatum significantly reduced viscosity. However, after an initial decrease in viscosity, further increases in the proportion of mineral oil beyond 21% w / w had little (if any) effect.
[0247] Changing the ratio of mineral oil to petrolatum did not affect the adhesion properties of Formulations 22, 23, and 24 ( Figure 4 ).
[0248] The adhesive layer thickness ( Figure 5 Each formulation maintained a higher layer thickness than the control ( Figure 5 (a)), potentially indicating an improved buffering effect.
[0249] The purpose of the above description is to illustrate some embodiments of the present invention, and it is not meant to be limiting. It is clear to those skilled in the art that various modifications and changes can be made to the device or program of the present invention without departing from the scope or spirit of the present invention.
[0250] Example 5: Clinical study
[0251] A study was conducted to evaluate the maximum maxillary bite force in a population of full maxillary denture wearers (42 subjects). The study compared the maximum incisor bite force of an experimental denture adhesive Formulation 25 with no adhesive prior to maxillary denture displacement over a 12-hour period. Formulation 25 was applied to the denture as a long continuous strip.
[0252]
[0253] Incisor bite force (BF) until maxillary denture displacement was measured at baseline and 0.5 h, 1 h, 3 h, 6 h, 9 h, and 12 h after denture insertion ( Figure 6 ).
[0254] Discover AOB 0-12 The data were statistically non-normally distributed, so additional post hoc analyses were performed to support the primary analysis. The post hoc analyses expressed bite force results as a percentage increase compared to baseline.
[0255]
[0256] The experimental denture adhesives were generally well tolerated. Preliminary analysis results indicated that the experimental denture adhesive formulation demonstrated statistically significant (p<0.05) greater bite force at 12 hours compared to no adhesive. Post hoc analysis supported the preliminary analysis results and demonstrated the efficacy of the experimental denture adhesive in improving denture retention at 12 hours compared to no adhesive.
Claims
1. A denture adhesive composition comprising: (a) carboxymethyl cellulose, (b) a cross-linked polyacrylic acid homopolymer and (c) an alkyl vinyl ether-maleic acid copolymer or a salt thereof.
2. The denture adhesive composition of claim 1, comprising: (a) about 15 to about 30 weight percent (% weight / weight) of carboxymethyl cellulose, (b) about 4 to about 15 weight percent (% weight / weight) of a cross-linked polyacrylic acid homopolymer and (c) about 15 to about 34 weight percent (% weight / weight) of an alkyl vinyl ether-maleic acid copolymer or a salt thereof.
3. The denture adhesive composition of claim 1 or 2, further comprising (d) an oil component and / or (e) a petrolatum component.
4. The denture adhesive composition of claim 1, 2 or 3, wherein the composition has (i) 500,000 to 2,000,000 centipoise (cP) at 25°C; 1° C.) and / or (ii) a pH of 4.0 to 10, in particular a pH of 5.0 to 8.
0.
5. The denture adhesive composition of claim 3 or 4, comprising: (d) from about 17 to about 26 weight % (% w / w) of an oil component and (e) from about 20 to about 30 weight % (% w / w) of petrolatum.
6. The denture adhesive composition of claim 5, wherein the carboxymethyl cellulose has a viscosity of about 1000 to about 2800 centipoise (cP) (measured in a 1% solution at 25°C).
7. The denture adhesive composition of claim 6, wherein the carboxymethyl cellulose consists of fine particles, at least 80% of which pass through a 200 US mesh sieve (equivalent to a 74 μm mesh sieve).
8. The denture adhesive composition of claim 6 or 7, wherein the carboxymethyl cellulose is sodium carboxymethyl cellulose.
9. The denture adhesive composition of any of the preceding claims, comprising from about 5 to about 10 wt % (% w / w) of a cross-linked polyacrylic acid homopolymer, in particular from about 6 to about 9 wt % (% w / w) of a cross-linked polyacrylic acid homopolymer.
10. The denture adhesive composition of claim 8, wherein the crosslinked polyacrylic acid homopolymer is an allyl pentaerythritol crosslinked homopolymer.
11. The denture adhesive composition of claim 10, wherein the cross-linked polyacrylic acid homopolymer is a type A or type B carbomer homopolymer.
12. The denture adhesive composition of claim 11, wherein the cross-linked polyacrylic acid homopolymer is Carbomer 971P NF and / or Carbomer 974P NF, in particular Carbopol 971P NF and / or Carbopol 974P NF.
13. The denture adhesive composition of any one of claims 9 to 12, wherein the alkyl vinyl ether-maleic acid copolymer or its salt is a poly(methyl vinyl ether / maleic acid) salt.
14. The denture adhesive composition of claim 13, wherein the alkyl vinyl ether-maleic acid copolymer or its salt is poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt.
15. The denture adhesive composition of any of the preceding claims comprising or consisting essentially of: (a) 26-30% w / w sodium carboxymethyl cellulose; (b) 6-9% w / w of a cross-linked polyacrylic acid homopolymer; (c) 16-20% w / w of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt; (d) 17-23% w / w of an oil component; (e) 23%-29% petrolatum; and optionally (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
16. The denture adhesive composition of claim 15 comprising, consisting of, or consisting essentially of: (a) about 28% weight / weight sodium carboxymethyl cellulose; (b) about 8% w / w of a cross-linked polyacrylic acid homopolymer; (c) about 18% weight / weight of poly(methyl vinyl ether / maleic acid) sodium-calcium mixed partial salt; (d) about 21% w / w of an oil component; (e) about 25% petrolatum; and optionally (f) at least one fragrance, colorant, preservative, surfactant or mixtures thereof.
17. The denture adhesive composition of claim 15 comprising, consisting of, or consisting essentially of: (a) about 28% weight / weight sodium carboxymethyl cellulose; (b) about 6% w / w of a cross-linked polyacrylic acid homopolymer; (c) about 20% weight / weight of a mixed partial salt of sodium-calcium poly(methyl vinyl ether / maleic acid); (d) about 21% w / w of an oil component; (e) about 25% petrolatum; and optionally (f) at least one flavoring agent, coloring agent, preservative, surfactant or mixtures thereof.
18. The denture adhesive composition of claims 15 to 17, wherein the composition has a viscosity of 1,000,000 to 2,000,000 centipoise (cP) and a pH of 5.0 to 7.
5.
19. The denture adhesive composition of any one of claims 1 to 16, wherein the composition is free of polyethylene glycol, sodium alginate, and zinc.
Citation Information
Patent Citations
Denture stabilizing compositions having improved hold
WO1992022280A1
Denture adhesive compositions
WO2013054236A1
Denture adhesive
WO2016091738A1
Improved denture adhesives
WO2018175826A1